2007
DOI: 10.1128/jvi.02848-06
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Rafts of Primary Endothelial Cells Are Essential for Kaposi's Sarcoma-Associated Herpesvirus/Human Herpesvirus 8-Induced Phosphatidylinositol 3-Kinase and RhoA-GTPases Critical for Microtubule Dynamics and Nuclear Delivery of Viral DNA but Dispensable for Binding and Entry

Abstract: Early during de novo infection of human microvascular dermal endothelial (HMVEC-d) cells, Kaposi's sarcoma-associated herpesvirus (KSHV) (human herpesvirus 8 [HHV-8]) induces the host cell's preexisting FAK, Src, phosphatidylinositol 3-kinase (PI3-K), Rho-GTPases, Diaphanous-2 (Dia-2), Ezrin, protein kinase C-ζ, extracellular signal-regulated kinase 1/2 (ERK1/2), and NF-κB signal pathways that are critical for virus entry, nuclear delivery of viral DNA, and initiation of viral gene expression. Since several of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
125
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(136 citation statements)
references
References 84 publications
9
125
1
1
Order By: Relevance
“…Constitutive macropinocytosis and membrane ruffling induced in oncogene-transformed fibroblasts have been shown to be due to constant activation of Src, PI3-K, and PLC-C (45). Our earlier studies have shown that disruption of LRs can increase global pSrc activity and viral entry, but lead into nonproductive infection (9). Hence, localized and regulated amplification of Src-PI3-K signaling in LRs by EphA2 appears to be crucial for productive KSHV entry.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Constitutive macropinocytosis and membrane ruffling induced in oncogene-transformed fibroblasts have been shown to be due to constant activation of Src, PI3-K, and PLC-C (45). Our earlier studies have shown that disruption of LRs can increase global pSrc activity and viral entry, but lead into nonproductive infection (9). Hence, localized and regulated amplification of Src-PI3-K signaling in LRs by EphA2 appears to be crucial for productive KSHV entry.…”
Section: Discussionmentioning
confidence: 94%
“…Disruption of HMVEC-d cell lipid rafts (LRs) by MβCD results in increased Src activation and virus entry. However, MβCD inhibits PI3K, RhoA, Dia-2, and NFκB activation; microtubule acetylation; nuclear delivery of viral DNA; and viral gene expression (3)(4)(5)(6)(7)(8)(9). Nuclear delivery of KSHV genomic DNA does not lead to lytic gene expression and progeny virus formation; instead, KSHV expresses its latent genes and establishes latency (3).…”
mentioning
confidence: 99%
“…It is of interest that apart from lytic infection, the interactions between gamma-herpeviruses and Rho GTPase signaling remain active even during non-productive infection, facilitating either the establishment of latency 41 or affecting cell motility and invasion and promoting the oncogenic properties of these viruses. 36,42 Less information is available for b-herpesviruses. During the initial phase of HCMV infection, total and activated-RhoA levels are decreased and this contributes to the disruption of actin stress fibers, 43 a phenomenon that facilitates HCMV nuclear translocation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role in entry of non enveloped the role of membrane rafts in entry of enveloped viruses has been investigated in studies using influenza virus (Orthomyxoviridae) [57][58][59][60][61], human immunodeficiency virus type 1 (HIV-1; Retroviridae) [62][63][64][65][66][67], human T lymphotropic virus 1 (HTLV-1; Retroviridae) [68,69], Ebola virus (Filoviridae) [70], Marburg virus (Filoviridae) [70,71], Epstein-Barr virus (EBV; herpesviridae) [72,73], herpes simplex virus-1 (HSV-1; herpesviridae) [74] including porcine herpesvirus-1 pseudorabies virus [75], human herpesvirus-6 (HHV-6; Herpesviridae) [76], human herpesvirus-8 (HHV-8; Herpesviridae) [77], vaccinia virus (Poxviridae) [78], coronavirus including severe acute respiratory syndrome coronavirus (SARS-CoV; Coronaviridae) [79][80][81][82][83][84][85], West Nile virus (WNV; Flaviviridae) [86], dengue virus (DEN; Flaviviridae) [87][88][89], Japanese encephalitis virus (JEV; Flaviviridae) [89], human hepatitis C virus (HCV; Flaviviridae) [90,91], Semliki Forest virus (Togaviridae) [92][93][94][95], Sindbis virus (Togaviridae) …”
Section: Role Of Membrane Rafts In Virus Entrymentioning
confidence: 99%
“…Phosphatidylinositol 3-kinase (PI3K), RhoAGTPase, and Diaphanous-2 (a RhoA-GTPase-activated adaptor molecule involved in microtubule activation) act as signal molecules in the entry process of the virus [77]. Reduction of HHV-8 infection and decrease in the cellular signals associated with viral infection in raft-disrupted cells suggest that membrane rafts in microvascular dermal endothelial cells are essential for HHV-8 infection and gene expression.…”
Section: Role Of Membrane Rafts In Virus Entrymentioning
confidence: 99%